HUBUNGAN ANTARA FUNGSI KOGNITIF DAN KUALITAS HIDUP PADA ANAK DOWN SYNDROME DI YPLB NUSANTARA DEPOK - Lutfiyah Nadza Hisanah (2023)
Background: In people with Down Syndrome, chromosome number 21 does not split into two, but has three, or trisomy. As a result, the baby has 47 chromosomes instead of the usual 46. This causes abnormalities in the physical and mental development of children with Down's Syndrome. This imperfect chromosome formation causes disturbances in cognitive function and quality of life during the child's growth phase. Method: This study used a correlational quantitative research design with a cross-sectional approach. With a sample of 83 children with Down Syndrome and with an error rate of 5%. This research was carried out offline through the cognitive scale for down syndrome (cs-ds) measurement tool and The TNO-AZL Questionnaire for Children's Health-Related Quality of Life (TacQol). Results: The results obtained in this study are that there is a significant relationship between cognitive function and gross motor skills in children with Down syndrome with a value of P = 0.000 for both variables and a correlation coefficient of r = 1.000 for cognitive function and r = 0.463 for quality of life . Because the value of r is positive for both variables, the relationship between the two variables is unidirectional. Conclusion: of this study resulted that there is a relationship between cognitive function and quality of life in the same direction in children with Down syndrome at YPLB Nusantara Depok.